2023
DOI: 10.1109/tvcg.2022.3146806
|View full text |Cite
|
Sign up to set email alerts
|

StrategyAtlas: Strategy Analysis for Machine Learning Interpretability

Abstract: Businesses in high-risk environments have been reluctant to adopt modern machine learning approaches due to their complex and uninterpretable nature. Most current solutions provide local, instance-level explanations, but this is insufficient for understanding the model as a whole. In this work, we show that strategy clusters (i.e., groups of data instances that are treated distinctly by the model) can be used to understand the global behavior of a complex ML model. To support effective exploration and understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In general, the number of instances and features that can be visually expressed with our approach has no intrinsic limit. Collaris and van Wijk [CVW22] found that usually the top 10–20 features were impactful for the tabular data sets they experimented with. For hundreds of features, it would be cognitively demanding for a human to analyse the influence of all these features at different levels of granularity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the number of instances and features that can be visually expressed with our approach has no intrinsic limit. Collaris and van Wijk [CVW22] found that usually the top 10–20 features were impactful for the tabular data sets they experimented with. For hundreds of features, it would be cognitively demanding for a human to analyse the influence of all these features at different levels of granularity.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal of such a procedure is to identify misclassified instances and interpret why this has happened [CdMP14], as well as improve predictive performance [SMGC14]. This scenario is where visual analytics (VA) approaches are considered as a possible solid solution [WDC*22] with many recent works focusing on problematic subsets of data for the interpretation and performance boost of ML models [CVW22, ZOS*23]. However, the classification problem becomes significantly more complex when the data set contains both class overlap and class imbalance .…”
Section: Introductionmentioning
confidence: 99%
“…In general, the number of instances and features that can be visually expressed with our approach has no intrinsic limit. Collaris and van Wijk [131] found that usually the top 10-20 features were impactful for the tabular data sets they experimented with. For hundreds of features, it would be cognitively demanding for a human to analyze the influence of all these features at different levels of granularity.…”
Section: Scalability For a Large Number Of Instances And Featuresmentioning
confidence: 99%
“…6. Collaris and van Wijk [131] also limited the number of instances to 5,000 in order to prevent overplotting issues in their projection-based view. Arguably, similar constraints should apply to our tool, especially for the UMAP projection and the inverse polar chart view.…”
Section: Scalability For a Large Number Of Instances And Featuresmentioning
confidence: 99%
See 1 more Smart Citation